The Accuracy of Computed Tomography-Based, Three-Dimensional Implant Planning in Robotic-Assisted Total Knee Arthroplasty - Marchand, Kevin B.; Salem, Hytham S.; Mathew, Kevin K.; Harwin, Steven F.; Mont, Michael A.; Marchand, Robert C. (The Journal of Knee Surgery, 2021)
Advanced imaging used in robotic-assisted total knee arthroplasty (TKA), such as computed tomography (CT)-based three-dimensional (3D) planning, may provide an accurate means of implant sizing preoperatively. The purpose of this study was to examine preoperative CT-based implant planning accuracy for robotic-assisted TKA in patients who have (1) varus deformities, (2) valgus deformities, (3) neutral alignment, and (4) retained hardware. A total of 393 patients underwent a robotic-assisted TKA by a single surgeon received preoperative CT scans. The surgeon reviewed the CT-based model preoperatively and recorded the expected size of the components. The final implants used in each case were recorded and compared with the surgeon's preoperative plan. In all groups of patients, the surgeon's CT-based implant plan was within one size of the implant utilized 100% of the time for both the tibiae and femora. Overall, the surgeon was exactly matched in 319 (81%) and 315 (80%) cases for the femoral and tibial components, respectively. For the femoral component, the mean age for patients in whom the original plan was exactly matched was younger than those whose implants were upsized and older than patients those implants were downsized (p = 0.024). Other patient demographics and preoperative knee alignment were not associated with predictive accuracy for femoral or tibial components. Our results demonstrate how preoperative CT-based, 3D planning for robotic-assisted TKA is accurate to within one size of the components in every case (100%), and exactly matched in 80%. The results of this study are important because they demonstrate how CT-based preoperative implant planning for TKA is reliable and accurate across all native knee alignments and other patient-specific factors. In addition, they build on a previous study by the same single surgeon, demonstrating that predictive ability can improve over time. This may be important as we move toward more outpatient surgery with less ability for prostheses inventory at ambulatory sites.
Keywords: osteoarthritis; knee; arthroplasty; computed tomography